Advanced exergy analysis and optimization of a CO2 to methanol process based on rigorous modeling and simulation. (1st October 2022) - Yang, Qingchun; Zhang, Zhi; Fan, Yingjie; Chu, Genyun; Zhang, Dawei; Yu, Jianhua
Graphical abstract: Highlights: Real improvement potential of CTM process is ascertained by advanced exergy analysis. 94.47% of the exergy destruction of the CTM process is endogenous. Avoidable exergy destruction of the CTM process is about 46.55%. Unavoidable endogenous exergy destruction of CTM process has the largest proportion. Total exergy destruction of the improved CTM process is reduced by 14.78%. Abstract: The efficient conversion and utilization of CO2 is of great strategic significance to achieve the goal of "carbon neutrality". The production of green methanol from the captured CO2 of industrial tail gas and green hydrogen of renewable energy can not only effectively reduce carbon emissions, but also solve the problem of green hydrogen storage and transportation. Facing with the unsatisfactory thermodynamic performance of CO2 to methanol (CTM) process, however, little literature has been reported on the systematic investigation of its thermodynamic performance to reduce its avoidable exergy destruction instead of spending wasted effort to reduce unavoidable one. This study conducted an advanced exergy analysis of the CTM process to ascertain its real improvement potential and interactions among the components. Results show that the real improvement potential of the CTM process is 46.55%. Most of the exergy destruction of the CTM process is endogenous, which accounts for 94.47% of the total exergy destruction. After combination of splitting the exergy destruction, it founds that the unavoidable endogenous exergy destruction of the CTM process has the largest proportion, 50.93%, followed by avoidable endogenous exergy destruction, 43.55%. Besides, several improvement strategies are proposed to reduce the avoidable exergy destruction, which indicate that the total exergy destruction of the improved CTM process is reduced by 14.78% and exergy efficiency is increased by 4.91%.